A general method to design dominant negatives to B-HLHZip proteins that abolish DNA binding - Krylov, Dmitry (The National Academy of Sciences of the USA, 1997)
We describe a method to design dominant-negative proteins (D-N) to the basic helix–loop–helix–leucine zipper (B-HLHZip) family of sequence-specific DNA binding transcription factors. The D-Ns specifically heterodimerize with the B-HLHZip dimerization domain of the transcription factors and abolish DNA binding in an equimolar competition. Thermal denaturation studies indicate that a heterodimer between a Myc B-HLHZip domain and a D-N consisting of a 12-amino acid sequence appended onto the Max dimerization domain (A-Max) is −6.3 kcal⋅mol(−1) more stable than the Myc:Max heterodimer. One molar equivalent of A-Max can totally abolish the DNA binding activity of a Myc:Max heterodimer. This acidic extension also has been appended onto the dimerization domain of the B-HLHZip protein Mitf, a member of the transcription factor enhancer binding subfamily, to produce A-Mitf. The heterodimer between A-Mitf and the B-HLHZip domain of Mitf is −3.7 kcal⋅mol(−1) more stable than the Mitf homodimer. Cell culture studies show that A-Mitf can inhibit Mitf-dependent transactivation both in acidic extension and in a dimerization-dependent manner. A-Max can inhibit Myc-dependent foci formation twice as well as the Max dimerization domain (HLHZip). This strategy of producing D-Ns may be applicable to other B-HLHZip or B-HLH proteins because it provides a method to inhibit the DNA binding of these transcription factors in a dimerization-specific manner.